Recent Advances in Intuitionistic Fuzzy Logic Systems Theoretical Aspects and Applications - Melliani, Said.; Castillo, Oscar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book aims at providing an overview of state-of-the-art in both the theory and methods of intuitionistic fuzzy logic, partial differential equations and numerical methods in informatics. It covers topics such as fuzzy intuitionistic Hilbert spaces, intuitionistic fuzzy differential equations, fuzzy intuitionistic metric spaces, and numerical methods for differential equations. It reports on applications such as fuzzy real time scheduling, intelligent control, diagnostics and time series prediction. Chapters were carefully selected among contributions presented at the second edition of the International Conference on Intuitionistic Fuzzy Sets and Mathematical Science, ICIFSMAS, held on April 11-13, 2018, at Al Akhawayn University of Ifrane, in Morocco. .
Construction of a Topological Degree theory in Generalized Sobolev Spaces -- Existence of positive solutions of nonlinear fractional quadratic differential equations -- Comments on fuzzy sets, interval type-2 fuzzy sets, general type-2 fuzzy sets and intuitionistic fuzzy sets -- Quotient Rings Induced Via Intuitionistic Fuzzy Ideals -- A fourth order Runge-Kutta Gill method for the numerical solution of intuitionistic fuzzy differential equations -- Task Parameter Impacts in Fuzzy Real Time Scheduling -- Framework for Optimization of Intuitionistic and Type-2 Fuzzy Systems in Control Applications -- Approximation of Intuitionistic Fuzzy Systems for Time Series Analysis in Plant Monitoring and Diagnosis -- New fractional derivative in Colombeau algebra -- Controlled fuzzy evolution equations -- Multiplication Operation and Powers of Trapezoidal Fuzzy Numbers -- Intuitioinistic fuzzy Hilbert space -- On Intuitionistic fuzzy Laplace transforms for second order intuitionistic fuzzy differential equations -- Approximate Solution of Intuitionistic Fuzzy Differential Equations by using Picard's method -- Fuzzy Cross Language Plagiarism Detection Approach Based on Semantic Similarity and Hadoop MapReduce -- Existence results for an impulsive fractional integro-differential equations with a non-compact semigroup -- Existence results of hybrid fractional integro-differential equations -- Convergence on intuitionistic fuzzy metric space -- Graphical Representation of Intuitionistic Membership Functions for its efficient use in Intuitionistic Fuzzy Systems -- Existence of mild solutions for an impulsive fractional integro-differential equations with non-local condition -- Fixed point theory, Contractive mapping, Fuzzy metric space -- Common fixed point theorems in b-Menger spaces -- On Intuitionistic Fuzzy Vector Spaces -- Time-dependent Neutral stochastic delay partial differential equations driven by Rosenblatt process in Hilbert space.
Keywords: Computational intelligence; Control engineering; Differential equations; Artificial intelligence; Computational Intelligence; Control and Systems Theory; Differential Equations; Artificial Intelligence